Moderator Effect of Halal Certified Awareness on Millennials and Generation Z Purchasing Decisions of Non-Halal Beauty Products - Juliana, Juliana; Mardiatunnisa, Mardiatunnisa; Rosida, Rida; Nasim, Arim; Budiwati, Neti; Azim, Mohammad; Rusydiana, Aam Slamet (Indonesian Journal of Halal Research, 2025)
This study examines the impact of beauty influencers, brand image, and awareness of halal certification on Muslim women’s purchasing decisions regarding non-halal certified beauty products, utilizing the Stimulus–Organism–Response (SOR) framework. Data were collected from 290 respondents and analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The model explains 74.4% of the variance in purchase decisions and 62.7% of the variance in attitude, indicating strong explanatory power. The results reveal that beauty influencers have a significant impact on brand image (β = 0.146, p < 0.01) and attitude (β = 0.072, p < 0.05), while brand image has a strong influence on attitude (β = 0.778, p < 0.001). Attitude has a substantial positive effect on purchase decisions (β = 0.677, p < 0.001) and mediates the impact of beauty influencers on purchasing behavior. In contrast, brand image does not directly influence purchase decisions. Furthermore, awareness of halal certification negatively affects purchasing decisions (β = –0.235, p < 0.001) and weakens the relationship between attitude and purchasing decisions (β = –0.076, p < 0.01). These findings underscore the pivotal role of consumer attitudes in shaping purchase intentions, while also highlighting the significance of halal awareness in the beauty industry. The study suggests that strengthening halal literacy and implementing strategic marketing are essential for enhancing consumer trust and supporting the growth of halal-certified beauty products.